Rapid and highly selective detection of chlorogenic acid in fruit samples by Fe3O4@SiO2@PIL with boron affinity via a fluorescence enhanced strategy. (12th December 2022) - Wan, Tiantian; Zhang, Zulei; Wang, Hailong; Yang, Yiwen; Yang, Hanxing; Zhang, Jian; Zeng, Yanbo; Li, Lei; Li, Jinchun
Abstract : Fe3 O4 @SiO2 @PIL showed good accessibility and displayed good affinity and excellent adsorption selectivity for CGA. Abstract : Chlorogenic acid (CGA), a cis -diol-containing compound, exhibits anti-inflammatory, antiviral, antimicrobial and anti-oxidation properties. Thus, selective determination of CGA in food products is extremely necessary. In this study, a boron affinity magnetic polymer named Fe3 O4 @SiO2 @PIL was synthesized to detect the concentration of CGA in actual fruit samples. The Fe3 O4 @SiO2 @PIL was characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transform infrared (FT-IR) spectroscopy, X-ray photoelectron spectroscopy (XPS) and thermogravimetric (TG) analysis. The results showed that the Fe3 O4 @SiO2 @PIL has uniform morphology, good magnetic properties, suitable structure and high stability. The experimental assays showed that the Fe3 O4 @SiO2 @PIL can detect the concentration of CGA within 7 min, and has a good linear relationship with CGA in the concentration range of 0.025–2 μM ( R 2 = 0.9989) with a detection limit of 10 nM (S/N = 3). Moreover, the Fe3 O4 @SiO2 @PIL exhibited excellent selectivity and can be reused for at least 5 runs, indicating its good stability and reusability. Finally, the Fe3 O4 @SiO2 @PIL was used to selectively separate CGA in real fruit samples with the recovery ranging from 93.4% to 103.0% and the relative standard deviation (RSD) between 0.7% and 5.1%. This study gives a new insight into the utilization of magnetic materials by grafting boric acid functionalized ionic liquids for specific and rapid detection of natural cis -diol-containing compounds.